Aisles of the Mandapa of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
The aisles of the mandapa (pillared hall) of the Bhandasar Temple have a curved arch ceiling with bands of floral motifs on the corner, and the rectangular portion is filled with blue cloud-like designs. In contrast to the multicoloured dome at the centre of the mandapa, this blue rectangular ceiling stands out.